Improve the Incremental Block Tariffs of Electricity: To Harmonize Pricing Policy Targets in the New Context of Power Supply and Demand in Vietnam - Bui, Xuan Hoi (International Journal of Energy Economics and Policy, 2021)
The existing retail electricity tariff for households in Vietnam is the incremental block structure. However, the most recent revision of the electricity tariff structure was in 2014 which it was 7 years - a long period of change in conditions of electricity supply and consumption leading to the need to adjust this structural price appropriately. This article provides an in-depth analysis of the current residential block tariff of residential electricity use to identify shortcomings, thereby, for building options to improve this incremental block tariff structure to ensure the harmonization of different pricing targets especially the equity, efficiency and promote the electricity saving, in the new context of electricity supply and demand in Vietnam. Keywords: Electricity pricing policy, incremental block tariff, Electricity of Vietnam JEL Classifications : D4, Q31, Q41, Q43. Q48 DOI: https://doi.org/10.32479/ijeep.11534